Comparative Analysis of Urinary Amylase and Serum Amylase in the Diagnosis and Prognosis of Acute Pancreatitis: A Cross-Sectional Study - Dr. Vajrang Akula, Dr. Natasha Mathias, Dr. Anurag Gudipati (South Eastern European Journal of Public Health, 2025)
Background: Acute pancreatitis (AP) is a major cause of emergency department visits, with a wide spectrum of severity ranging from mild, self-limited, to severe life-threatening conditions. The current diagnostic limitations of the commonly used biomarkers, serum amylase and lipase, necessitate alternative markers. The diagnostic accuracy of urinary amylase versus that of serum amylase and lipase levels in AP was studied. Objectives: The ability of urinary amylase to be used diagnostically in acute pancreatitis has been assessed, and its efficacy compared with serum amylase and lipase for detecting and monitoring disease severity. Methods: Fifty-five patients diagnosed with AP at Yenepoya Medical College Hospital between January 2021 and December 2022 were included in this cross-sectional study. We measured urinary amylase and serum amylase levels at admission, 24 h, 48 h, and discharge. ROC curve analysis was used to evaluate sensitivity, specificity, and diagnostic accuracy. Results: The AUC, sensitivity, and specificity of urinary amylase (0.878, 95%, and 92%, respectively) were better than those of serum amylase (0.532) and lipase (0.655). Measuring urine amylase allowed superior monitoring of patients because this measure remained elevated for longer than the serum markers. Ethanol consumption was the most common etiology (72.73%), with gallstones (27.27%) being the second most common. The overall death rate was 1.82% in severe cases. Conclusion: Acute pancreatitis is a sensitive, specific, and prolonged diagnostic marker in the form of urinary amylase, which surpasses serum markers for early diagnosis and disease monitoring. Routine urinary amylase testing is recommended to improve clinical management.